2020
DOI: 10.2147/cmar.s233123
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hepatic Arterial Infusion Oxaliplatin Plus Oral S-1 Chemotherapy in Gastric Cancer with Unresectable Liver Metastases: A Case Series and Literature Review</p>

Abstract: The use of hepatic artery infusion (HAI) as a regional therapy against liver metastasis has rarely been reported in gastric cancer. This study aimed to evaluate the efficacy and safety of HAI oxaliplatin plus oral S-1 chemotherapy in first-line palliative therapy for gastric cancer with multiple liver metastases (GCLM). Methods: We reviewed the records of five patients with GCLM who received HAI oxaliplatin (70-80 mg/m 2 2 hrs d1,15) administered via a port-catheter system and S-1 with oral (35-40 mg/m 2 twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It also features a catheter-connected exit. The fluid container applied for charging consists of fluorocarbon liquid which is warmed by using the temperature of patient's body and changed to a gas phase, which keeps the drug chamber at a constant pressure [ 16 , 17 ]. The pressure applied by the vapor in homeostasis with the steady liquid phase and independent of volume at a given temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It also features a catheter-connected exit. The fluid container applied for charging consists of fluorocarbon liquid which is warmed by using the temperature of patient's body and changed to a gas phase, which keeps the drug chamber at a constant pressure [ 16 , 17 ]. The pressure applied by the vapor in homeostasis with the steady liquid phase and independent of volume at a given temperature.…”
Section: Methodsmentioning
confidence: 99%
“…However, LM is a life-threatening disease to be cared for in BC [9]. HAIC has been used to treat gastrointestinal malignancies with LM expecting high tumor response followed by extended survival rate with low toxicity [10][11][12]. However, the benefit of HAIC for BC patients with LM remains unclear although some retrospective studies reported that HAIC was effective for LM refractory to conventional systemic chemotherapy [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers have turned their attention to the application of HAIC in GCLM. Wang et al reviewed five GCLM patients who received HAI oxaliplatin and S-1 oral treatment, the objective response rate was 40%, the disease control rate was 80%, and HAI chemotherapy had better local control of liver metastasis, with a median PFS of 8.8 months (21). Ojima et al retrospectively evaluated the efficacy of HAIC for synchronous GCLM, ORR of HAIC was 83%, there were no serious side effects, and the median survival time (MST) of the HAIC group was 19.2 months (22).…”
Section: Introductionmentioning
confidence: 99%